Psychosocial Correlates of Sun Protection Behaviors among U.S. Hispanic Adults - Coups, Elliot J. (2014)
The incidence of skin cancer among U.S. Hispanics increased 1.3% annually from 1992 to 2008. However, little research has focused on skin cancer prevention among the rapidly growing Hispanic population. In this study, we examined theory-driven, psychosocial correlates of sun protection behaviors in a population-based sample of 787 Hispanic adults (49.6% female, mean age = 41.0 years) residing in five southern or western U.S. states. Participants completed an English- or Spanish-language online survey in September 2011. The outcomes of focus were sunscreen use, shade seeking, and use of sun protective clothing. The correlates included suntan benefits, sun protection benefits and barriers, skin color preference, perceived natural skin protection, photo-aging concerns, perceived skin cancer risk, skin cancer worry, skin cancer fatalism, and sun protection descriptive norms. Results of multiple linear regression analyses revealed the following: sun protection barriers were negatively associated with each outcome; descriptive norms were positively associated with each outcome; perceived natural skin protection was inversely associated with sunscreen use; skin cancer worry was positively associated with shade seeking and use of sun protective clothing; skin cancer fatalism was negatively associated with shade seeking; and skin color preference was negatively associated with use of sun protective clothing. A number of additional statistically significant associations were identified in bivariate correlation analyses. This study informs the potential content of interventions to promote engagement in sun protection behaviors among U.S. Hispanics.